Pengembangan Peternakan Sapi Potong untuk Peningkatan Perekonomian Provinsi Jawa Tengah: Suatu Pendekatan Perencanaan Wilayah - Yuliana Susanti; Dominicus Savio Priyarsono; Sri Mulatsih (Jurnal Agribisnis Indonesia, 2014)
Beef cattle development based on regional planning approach is one of efforts to increase the role of beef cattle in Central Java Province, by synergizing between its commodity and the region potency. This study aims to analyze the role of beef cattle in the economy of Central Java and its potential development based on regional planning. The analysis instrument used to answer the aim of this research is descriptive analysis, LQ (Location Quotient), KPPTR (Ruminant Population Increased Capacity) and schallogram analysis. The results showed that the role of beef cattle in Central Java Province make a positive contribution to fulfill the demand for beef, but the beef cattle contribution for GDRP and labor is still relatively small. Central Java has considerable potency for the development of beef cattle since it is even now able to increase the ruminant population amounting 5.232.130 AU (Animal Unit) based on TDN (Total Digestible Nutrient), which scattered in 17 districts of the 21 districts designated as the development regions of beef cattle. The base region of beef cattle in Central Java Province located in 7 (seven) districts, but based on the results of the physical assessment of services capacity of these regions considered remain relatively low and middling. The strategy to increase the role of beef cattle in the economy of Central Java is by classifying the regions into 4 groups: namely based on the source of forage, the region base of beef cattle, and the level of service capacity of beef cattle development.